On the writing of New Testament commentaries : festschrift for Grant R. Osborne on the occasion of his 70th birthday - Porter, Stanley E., 1956-; Schnabel, Eckhard J.; Osborne, Grant R. (Texts and Editions for New Testament Study, 2013)
The essays in On the Writing of New Testament Commentaries discuss historical, hermeneutical, methodological, literary, and theological questions that shape the writing of commentaries on the books of the New Testament. While these essays honor Grant R. Osborne, they also represent the first sustained effort to systematically address commentary writing in the field of New Testament studies.